Serum levels of the soluble haemoglobin scavenger receptor CD163 in MPO-ANCA-associated renal vasculitis. (2nd September 2016) - Nagai, M; Hirayama, K; Ebihara, I; Higuchi, T; Shimohata, H; Kobayashi, M
Abstract : Objectives : The contribution of infections to the mortality of patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is important, and early and careful infection control is necessary. We investigated the usefulness of the serum-soluble haemoglobin scavenger receptor CD163 for detecting the presence of infectious complications regardless of disease activity. Method : Soluble CD163 in serum obtained from 45 Japanese patients with myeloperoxidase (MPO)-AAV was measured by an enzyme-linked immunosorbent assay (ELISA). We evaluated 36 samples from active-vasculitis patients, 36 samples from inactive-vasculitis patients without infection, and 19 samples from inactive-vasculitis patients with infectious complications. Serum-soluble CD163 was also measured in 15 infectious patients without vasculitis and in 30 normal controls. Results : The mean serum-soluble CD163 level was higher in the patients with infectious complications than in the active-vasculitis patients, inactive-vasculitis patients, and normal controls. There were significant positive correlations between serum-soluble CD163 levels and white blood cell (WBC) count, serum C-reactive protein (CRP) levels, and serum albumin levels, but only serum CRP levels were correlated with serum-soluble CD163 levels in a multiple regression analysis. On the receiver-operating characteristic (ROC) curve, serum-soluble CD163 levels had 80.6% sensitivity and 86.7% specificity for differentiating patients with infection from those without infection. Among the active-vasculitis patients, the mean serum-soluble CD163 level of the patients with alveolar haemorrhage was significantly lower than that of the patients with interstitial lung diseases and that of the patients without pulmonary lesions. Conclusions : The serum-soluble CD163 level may be a useful marker for the detection of infectious complications in MPO-AAV patients.